DFT Study of Cs/Sr/Ag Adsorption on Defective Matrix Graphite - Zengtong Jiao; Xiaotong Chen; Chao Fang; Gang Xu; Chi Zhang; Luhao Fan; Bing Liu (Science and Technology of Nuclear Installations)
The geometries, adsorption energies, and electronic structures of Cs, Sr, and Ag atoms on matrix graphite surface with point defects were calculated and analyzed using the density functional theory (DFT) and the Perdew–Burke–Ernzerhof (PBE) formulation of the generalized gradient approximation (GGA). Three different types of point defects, i.e., single vacancy and “bridge” and “spiro” interstitials are considered using approximate van der Waals (vdW) correction methods. The results of adsorption energies show that the metal fission products of Cs, Sr, and Ag are more stable on single vacancy defects than “bridge” or “spiro” interstitial defects. This is further confirmed by the analysis of electronic structures, such as charge density difference (CDD) and density of state (DOS). All these results indicate that dangling bonds play an important role in the adsorption behaviors of metallic fission products on matrix graphite.